Argument-Driven Inquiry Assisted by Lumi Education: Improving Students' Scientific Argumentation Skills on Static Electricity - Salsabila, Putri Avianita; Hendratmoko, Ahmad Fauzi; Roqobih, Fikky Dian (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
The aim of this study is to evaluate the effectiveness of the Argument-Driven Inquiry (ADI) learning strategy, supported by the Lumi Education platform, in enhancing the scientific argumentation skills of students related to static electricity. A quasi-experimental approach, employing a non-equivalent control group, was adopted in this study, including two ninth-grade classes in a junior high school as participants. The participants were exposed to instruction utilizing either the ADI strategy and the support of the Lumi Education website or standard instruction as a control group. The strategies developed included a scientific argumentation skills test, designed as a claim, evidence, and warrant procedure, as well as a questionnaire administered among students. The data gathered were statistically processed by comparing pre-test and post-test results, calculating the normalized gains, as well as a description analysis approach among the students' written responses. The results show that, compared to a low category average normalization gain of 0.18 among the control class, a significantly high average value, 0.70, was established by the experimental class, signifying a statistically significant difference between the two categories, yielding a significance at a probability value less than 0.001. The results among the experimental class developed a Cohen's value, or the standardized effect size, estimated as 0.53, signifying a medium effect, while among the control class, an estimated 0.11, signifying a small effect, was recognized. Students said they liked the learning experience and thought it was more interesting, dynamic, and simpler to comprehend when they worked together on real-world tasks. However, some still encountered difficulties with conceptual comprehension and problem-solving. These findings imply that integrating ADI with digital scaffolding, such as Lumi Education, can effectively strengthen scientific argumentation skills while promoting active and reflective learning.